CHILDREN LISTENING ABILITY THROUGH CARTOON VIDEOS: A CASE STUDY IN BATAHAN VILLAGE - Aida Parista; Sartika Dewi Harahap (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Listening is a fundamental language skill that plays a crucial role in early childhood English acquisition. This study aims to describe the listening ability of children aged 4–5 years through the use of cartoon videos as a learning medium in Batahan Village, North Sumatra. This research employed a qualitative case study design involving three children as participants. Data were collected through observation, interviews with parents, and documentation, and analyzed using Miles and Huberman’s qualitative data analysis model. The findings reveal that cartoon videos positively influence children’s listening skills, attention, and learning motivation. Children were able to recognize characters, understand basic activities, follow simple instructions, and respond emotionally to the story. However, differences in listening development were observed among the children, indicating that individual characteristics such as attention span and learning style affect learning outcomes. The study concludes that cartoon videos are effective instructional media for developing listening skills in early childhood, particularly when supported by active guidance from teachers and parents.